The current status of management accounting in Romania: the accountants' perception - Corina Grosu; Alina Almasan; Cristina Circa (Journal of Accounting and Management Information Systems (JAMIS), 2014)
The purpose of this paper is to investigate the accountants' perceptions as providers of accounting information, regarding the status of the management accounting in the Romanian business environment. In this respect we conducted a questionnaire-based study among accounting professionals from the Timis County. The study shows that the accountants' perception on management accounting is strongly influenced by factors like: the taylorian mentality, lack of interest, motivation and initiative, as well as the excessive focus on the financial and fiscal reporting, making us doubt the usefulness of the management accounting in the Romanian business accounting. This paper fills a current gap in the management accounting literature, as the existing papers focus rather on the managers' perception than on the accountants' perception. It is an interesting topic in the Romanian context because the atypical evolution of the accounting led to the neglection of the management accounting field, with its enormous informative potential
Keywords: M41; 650; management accounting; accountants' perception; mentalities; attitudes